2014
DOI: 10.1037/bne0000019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lesions to the postsubiculum or the anterior dorsal nucleus of the thalamus on spatial learning in rats.

Abstract: To investigate the role of the head direction (HD) cell circuit in spatial navigation, rats with bilateral, neurotoxic lesions to the postsubiculum (PoS; Experiment 1) or the anterior dorsal nucleus of the thalamus (ADN; Experiment 2) were compared to sham controls on 2 tasks that could be solved using directional heading. Rats were first trained on a direction problem in a water T maze where they learned to travel either east or west from 2 locations in the experimental room. ADN lesioned rats were impaired r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…While control animals typically swam toward the relative location within the pool, animals with an inactivated anterodorsal thalamus showed an overwhelming preference for the absolute location. In a complementary study using a water T-maze, Peckford et al (2014) confirmed that directional navigation was impaired after anterodorsal thalamic lesions. These findings collectively suggest that the anterodorsal thalamus is involved in processing information regarding the direction of movements, but the retrieval of the absolute location of the platform in relation to the distal cues was seemingly maintained after inactivation.…”
Section: Allocentric Navigationmentioning
confidence: 63%
“…While control animals typically swam toward the relative location within the pool, animals with an inactivated anterodorsal thalamus showed an overwhelming preference for the absolute location. In a complementary study using a water T-maze, Peckford et al (2014) confirmed that directional navigation was impaired after anterodorsal thalamic lesions. These findings collectively suggest that the anterodorsal thalamus is involved in processing information regarding the direction of movements, but the retrieval of the absolute location of the platform in relation to the distal cues was seemingly maintained after inactivation.…”
Section: Allocentric Navigationmentioning
confidence: 63%
“…However, a major limitation to interpreting these studies as demonstrating that HD cells are used in navigation comes from the absence of specificity afforded by a lesion. For example, lesions to areas such as the mammillary bodies [21] or anterior thalamus [18,20] likely have broader effects on learning and memory in addition to their effects on HD cells [37,38]. In addition, if the effects that these lesions have on behavior are due to knocking out the HD signal, it is unclear why lesions further upstream in the network have greater effects than lesions in, for example, downstream cortical regions [20].…”
Section: Discussionmentioning
confidence: 99%
“…The other approach to explore the role of HD cells in behavior has shown that lesions of areas involved in the HD signal leads to various deficits in spatial ability [18][19][20][21]. However, a major limitation to interpreting these studies as demonstrating that HD cells are used in navigation comes from the absence of specificity afforded by a lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations